Forage yield and nutritive value of plantain and chicory for livestock feed at high altitudes in Peru - Vallejos Fernández, Luis A. (2024)
Background: Evaluation of forage resources is vital for the sustainability of livestock farming in the South American Andes, especially under conditions of low water availability for irrigation and acid soils. Methods: We evaluated the productivity and nutritive value of two cultivars of chicory (Cichorium intybus L.) and one of plantain (Plantago lanceolata L.) in three high‐altitude sites (AL) of the northern highlands of Peru: AL‐I: 2300–2800 m.a.s.l, AL‐II: 2801–3300 m.a.s.l. and AL‐III: 3301–3800 m.a.s.l., for 1 year. The parameters evaluated were dry matter yield (DMY), plant height (PH), growth rate (GR) and nutritional value. Results: Plantain achieved the greatest annual DMY (ADMY), PH and GR compared to the two chicory cultivars (9.34, 9.56 and 13.39 Mg ha−1 for Puna II and Sese 100 chicory and Tonic plantain, respectively; p = 0.0019). The greatest ADMY and GR occurred at AL‐I. Regarding nutritional value, differences were observed only for in vitro digestibility of dry matter and metabolisable energy with chicory cultivars higher than plantain. Conclusions: The results indicate that the three cultivars evaluated may be used as a nutritional supplement in cattle feed, associated with grasses because they have high nutritive value suitable for milk production in the mountain regions of Peru.